The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1111/hex.12057
|View full text |Cite
|
Sign up to set email alerts
|

Communication relating to family members' involvement and understandings about patients' medication management in hospital

Abstract: Background Many patients with complex health-care needs are prescribed several medications on a daily basis. With admission to hospital, patients are often placed in a vulnerable position. Family members can therefore play an important role in supporting patients in decision making about managing medications and negotiating communication exchange with health professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 19 publications
2
36
0
Order By: Relevance
“…144,[146][147][148][149][150][151][152][153][171][172][173] However, while these studies utilise qualitative methods to capture information about the pharmacist-patient interaction occurring in either hospital or ambulatory clinic settings, most are atheoretical, some lack detail about the methods used and most do not directly address our project's aim to examine aspects of effective communication.…”
Section: -170mentioning
confidence: 99%
See 4 more Smart Citations
“…144,[146][147][148][149][150][151][152][153][171][172][173] However, while these studies utilise qualitative methods to capture information about the pharmacist-patient interaction occurring in either hospital or ambulatory clinic settings, most are atheoretical, some lack detail about the methods used and most do not directly address our project's aim to examine aspects of effective communication.…”
Section: -170mentioning
confidence: 99%
“…Instead, family members observed pharmacists or pharmacy staff to mostly be delivering and stocking medication supplies. 172 Researchers interviewed physicians, nurses, pharmacists as well as patients and their families in specialty hospital settings to find out the barriers and facilitators in engaging patients and their families in conversations about managing medications. 173 Family members and patients stated that they were often hesitant to request information and to discuss issues about their medications as they observed that healthcare professionals often appeared very busy.…”
Section: -170mentioning
confidence: 99%
See 3 more Smart Citations